PACE: A new approach to dynamic voltage scaling - Lorch, Jacob R.; Smith, Alan Jay; Lorch, Jay (IEEE Transactions on Computers, 2004)
By dynamically varying CPU speed and voltage, it is possible to save significant amounts of energy while still meeting prespecified soft or hard deadlines for tasks; numerous algorithms have been published with this goal. We show that it is possible to modify any voltage scaling algorithm to minimize energy use without affecting perceived performance and present a formula to do so optimally. Because this formula specifies increased speed as the task progresses, we call this approach PACE (Processor Acceleration to Conserve Energy). This optimal formula depends on the probability distribution of the task’s work requirement and requires that the speed be varied continuously. We therefore present methods for estimating the task work distribution and evaluate how effective they are on a variety of real workloads. We also show how to approximate the optimal continuous schedule with one that changes speed a limited number of times. Using these methods, we find we can apply PACE practically and efficiently. Furthermore, PACE is extremely effective: Simulations using real workloads and the standard model for energy consumption as a function of voltage show that PACE can reduce the CPU energy consumption of existing algorithms by up to 49.5 percent, with an average of 20.6 percent, without any effect on perceived performance. The consequent PACE-modified algorithms reduce CPU energy consumption by an average of 65.4 percent relative to no dynamic voltage scaling, as opposed to only 54.3 percent without PACE.